Challenges and Opportunities Raised by Covid-19 for the Judicial Systems in Europe - Claudia Cavicchioli (Firenze University Press, 2021)
This contribution examines and analyses the challenges and opportunities created by the spread of Covid-19 for the European justice systems, putting them in relation with educational needs that are arising. The Covid-19 crisis has acted as a stress test, as unexpected as it is energic, for the resilience of national systems and has shed light on the lack or delay in the digitalisation of justice systems, whereas throughout Europe, due to the limited availability of the national systems, recourse to alternative dispute resolution mechanisms has increased. The adjustments that have been made necessary to deal with the period of Covid-19 could radically and permanently change the way justice will be rendered in the post-pandemic world, also creating an opportunity for evolution and modernisation. The need to draw on shared best practices for the development of new protocols to ensure an effective functioning of the justice system must be balanced with the respect of fundamental rights such as access to justice and right to a fair trial. To this end, all stakeholders in the judiciary face a steep learning curve for developing new skills necessary to actively and consciously take part in the paradigm shift that justice is encountering.   Sfide e opportunità create dal Covid-19 per i sistemi giudiziari in Europa.   Questo contributo prende in esame e analizza le sfide e le opportunità create dalla diffusione del Covid-19 per i sistemi giudiziari europei, mettendole in relazione con i bisogni formativi che stanno emergendo. La crisi legata al Covid-19 ha costituito uno stress test, inatteso quanto energico, per la resilienza dei sistemi nazionali e ha messo in evidenza la mancanza o il ritardo della digitalizzazione dei sistemi di giustizia, mentre in tutta Europa, a causa della disponibilità limitata dei sistemi nazionali, si è assistito ad un aumentato ricorso a modi alternativi di risoluzione delle controversie. Gli adeguamenti che si sono resi necessari durante il periodo del Covid-19 potrebbero modificare radicalmente e permanentemente il modo in cui la giustizia sarà resa nel mondo post-pandemico, creando anche opportunità di evoluzione e modernizzazione. La necessità di attingere a best practices condivise per lo sviluppo di nuovi protocolli e procedure atti a garantire un funzionamento efficace deve essere contemperata con il rispetto dei diritti fondamentali, quali l'accesso alla giustizia e il diritto ad un giusto processo. A tale scopo, tutte le parti interessate nel settore giudiziario si trovano ad affrontare una curva di apprendimento ripida per lo sviluppo delle nuove competenze necessarie ad una partecipazione attiva e consapevole al cambiamento di paradigma che la giustizia sta affrontando.